Formulation and Evaluation of Polyherbal Hair Oil for Antioxidant and Antimicrobial Activity - Shaily Mishra,; Nikhil Sharma,; Dr. Shamim Ahmad, (Asian Journal of Pharmaceutical Research and Development, 2025)
Hair is an essential element of the human body that significantly enhances physical appearance. This study aims to scientifically evaluate the formulation and characteristics of a polyherbal hair oil using ingredients such as amla, hibiscus, curry leaves, and coconut oil. The herbal formulation was prepared using a boiling method and exhibited multiple benefits including anti-hair loss, anti-dandruff, anti-fungal, and anti-greying effects, along with improved scalp blood circulation.The study involved the assessment of various physicochemical properties of the prepared oil such as acid value, viscosity, saponification value, pH, and skin irritation potential. With the increasing prevalence of hair-related problems such as alopecia, hair thinning, premature greying, dryness, and dandruff due to modern lifestyle factors, the need for natural, safe, and effective hair care solutions has grown.The formulated polyherbal oil was found to be rich in bioactive compounds including flavonoids, tannins, and phenolic compounds, showing promising antioxidant and antimicrobial activity. The study supports the potential of polyherbal formulations in managing hair disorders and enhancing hair and scalp health.